Effects of valproate and carbamazepine monotherapy on neuroactive steroids, their precursors and metabolites in adult men with epilepsy - Hill, Martin; Zárubová, Jana; Marusič, Petr; Vrbíková, Jana; Velíková, Marta; Kancheva, Radmila; Kancheva, Lyudmila; Kubátová, Jana; Dušková, Michaela; Zamrazilová, Ludmila; Kazihnitková, Hana; Simůnková, Kateřina; et al. (The Journal of steroid biochemistry and molecular biology, 2010)
Only limited data is available concerning the role of unconjugated Δ(5) C19-steroids and almost no data exists regarding the neuroactive C21 and C19 3α-hydroxy-5α/β-metabolites in men with epilepsy. To evaluate the alterations in serum neuroactive steroids and related substances in adult men with epilepsy on valproate and carbamazepine monotherapy, we have measured 26 unconjugated steroids, 18 steroid polar conjugates, gonadotropins and sex hormone binding globulin (SHBG) in 6 and 11 patients on valproate and carbamazepine monotherapy, respectively, and in 19 healthy adult men, using the GC-MS and immunoassays. Decreased testosterone, free androgen index, free testosterone, androstenediol, 5α-androstane-3α,17β-diol (androstanediol), androsterone, epiandrosterone, DHEA, 7β-hydroxy-DHEA, and DHEAS levels were associated with epilepsy per se. Valproate (VPA) therapy increased 5α-dihydrotestosterone, androsterone, epiandrosterone, DHEA, DHEAS, and 7β-hydroxy-DHEA levels. Decrease in pregnenolone and 17-hydroxypregnenolone were associated with epilepsy with no effect of antiepileptic drugs (AEDs). Alternatively, the increase in progesterone levels was linked to epilepsy and VPA further increased progesterone levels. Reduced steroid 20α-hydroxy-metabolites and cortisol were connected with epilepsy without an effect of AEDs. Carbamazepine induced only slight decrease in isopregnanolone, 5α,20α-tetrahydroprogesterone, and androstanediol levels.
Keywords: Carbamazepine; Steroids; Male; gonadotropiny; plynová chromatografie s hmotnostně spektrometrickou detekcí; Adult; Gonadotropins; Sex Hormone-Binding Globulin; dospělí; mužské pohlaví; Anticonvulsants; epilepsie; Gas Chromatography-Mass Spectrometry; karbamazepin; lidé; Humans; testosteron; androstany; antikonvulziva; pregnenolon; Androstanes; Valproic Acid; steroidy; Epilepsy; Testosterone; Pregnenolone; kyselina valproová; globulin vázající pohlavní hormony